Pre- and Post-Birth Components of Intergenerational Persistence in Health and Longevity: Lessons from a Large Sample of Adoptees - Evelina Björkegren; Mikael Lindahl; Mårten Palme; Emilia Simeonova (Institute of Labor Economics (IZA), 2019)
We use data on a large sample of Swedish-born adoptees and their biological and adopting parents to decompose the persistence in health inequality across generations into pre-birth and post-birth components. We use three sets of measures for health outcomes in the second generation: mortality, measures based on data on hospitalization and, finally, measures using birth outcomes for the third generation. The results show that all of the persistence in mortality is transmitted solely via pre-birth factors, while the results for the hospitalization measures suggest that at least three quarters of the intergenerational persistence in health is attributable to the biological parents.
Keywords: I10; I14; 330; health inequality; intergenerational transmission; nature and nurture